Space cooling load monitoring system with IoT - Miqdad, A.; Kadir, Kushsairy; Ahmed, Syed Faiz; Janin, Zuriati; Khan, Sheroz (IEEE, 2016)
Collecting large amount of data are made easier and simpler by taking advantage of Wireless Sensor Network and Internet of Thing technology. Rampant use of these technology in today’s time have made it inexpensive and cost effective to be applied as research tools. The action of saving data over long period of time can be done flawlessly by maximizing the big capacity of cloud storage. This paper presents the application of WSN and IoT technology to monitor and record data of real time current usage for split unit air conditioners placed in classroom. The classroom uses two air conditioners with 4HP to control its ambient temperature. Microcontroller is utilized to transmit the data collected by current clamp sensor to the cloud server over the internet.